TEAM-PAIR-SOLO TECHNIQUE TO TEACH READING COMPREHENSION OF EXPLANATORY TEXT - Hapsari, Endah Woro; ., Sudarsono; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Email: endahworohapsari@rocketmail.com Abstract: The purpose of this research was to investigate the level of the effectiveness of team-pair-solo to teach reading comprehension of explanatory text to Year-X students of ?SMA Negeri 8 Pontianak? in Academic Year 2014/2015. This research was a pre-experimental research with one group pre-test and post-test design. The population of this research were students of Year-X MIA. The samples of this research were Year-X MIA1. The technique of data collecting was measurement technique. The data were collected by applying pre-test and post-test through team-pair-solo to teach reading comprehension of explanatory text. The students score on pre-test and post-test was analyzed by using SPSS. The final computation shows that the effect size of the treatment was 0.904 (> 0.5) and considered very effective. It proves that the use of team-pair-solo was highly-effective to teach reading comprehension of explanatory text to Year-X MIA1 students. Key Words: Team-Pair-Solo, Reading Comprehension, Explanatory Text. Abstrak: penelitian ini bertujuan untuk mengetahui tingkat keefektifan pengunaan tehnik team-pair-solo dalam mengajarkan pemahaman membaca teks explanatory kepada siswa kelas X ?SMA Negeri 8 Pontianak? pada tahun ajaran 2014/2015. Penelitian ini adalah sebuah penelitian eksperimental dengan rancanggan satu grup pre-test dan post-test. Populasi dalam penelitian ini adalah siswa-siswa kelas X ilmu alam. Sample penelitian ini adalah siswa kelas X ilmu alam satu. Teknik pengumpulan data adalah teknik pengukuran. Data-data diambil dengan menerapkan pre-test dan post-test melalui penggunaan teknik team-pair-solo dalam mengajarkan pemahaman membaca teks explanatory. Nilai siswa pada pre-test dan post-test kemudian dianalisa menggunakan SPSS. Perhitungan akhir menunjukkan bahwa effect size dari perlakuan adalah 0.904 (> 0.5) dan dikatakan sangat efektif. Hal tersebut membuktikan bahwa penerapan tecknik team-pair-solo sangat efektif untuk mengajar pemahaman membaca teks explanatory untuk siswa kelas X ilmu alam satu. Kata kunci: team-pair-solo, pemahaman membaca, teks explanatory.